Kewenangan Pemerintah Desa dalam Penyediaan Air Bersih di Desa Ciledug Kulon - Diennur Padilah Pratama Iskandar; Moh. Sigit Gunawan; Solichin (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the implementation of the Ciledug Kulon Village Government's authority regarding clean water provision, as well as the legal issues encountered during its execution. The research employs an empirical legal method, utilizing both statutory and field-based approaches. The findings indicate that the provision of water storage tanks (fiberglass tanks) by the Ciledug Kulon Village Government constitutes an exercise of village-scale local authority in accordance with Law Number 6 of 2014 concerning Villages. However, implementation remains suboptimal due to a lack of alignment regarding the division of authority with the local government, as well as limitations in infrastructure, budget and inter-agency coordination. Strengthening the exercise of this authority requires synergy between the village and local governments, support for clean water infrastructure development, institutional strengtheningand the establishment of legal instruments at the village level.